Teachers’ Beliefs and Practice on Providing EFL Written Corrective Feedback - Annury, Muhammad Nafi; Ma'mun, Nadiah; Sutrisno, Djoko (Journal of English Teaching and Learning Issues, 2023)
This study analyzes how and why writing instructors provide written corrective feedback (WCF) on academic writing tasks. It was an ethnography study conducted by the Department of English Education at University in Semarang, Indonesia. This study investigated and analyzed the attitudes of teachers to get insight into classroom methods for delivering written corrective feedback (CF) on student writing. The major objective of the study was to evaluate instructors' beliefs and practices. Therefore, the teachers' perspectives on providing written corrective feedback (WCF) were required to determine the true answers and provide corrective feedback. The conceptual basis for this study was developed from Borg's (2003) concept of teacher cognition (beliefs) and practices, as well as the impediments to written CF reported by several writers. This recent study conducted interviews with three English Education Department instructors who instructed writing classes. This investigation utilized classroom observation, the think-aloud technique, and in-depth interviews. The data was examined using Spradley's technique (1979, 1980). The study of the data revealed both congruence and discord between the beliefs and actions of lecturers. For instance, the instructors' focus and number of writing CF were consistent. In addition, it was demonstrated that extraneous influences affected the lecturers' application of their theories.